Prognostic Impact of Radiological Consolidation Tumor Ratio in Clinical Stage IA Pulmonary Ground Glass Opacities - Xi, Junjie; Yin, Jiacheng; Liang, Jiaqi; Zhan, Cheng; Jiang, Wei; Lin, Zongwu; Xu, Songtao; Wang, Qun (Frontiers in Oncology, 2021)
Objectives: Our study aimed to validate pathologic findings of ground-glass nodules (GGOs) of different consolidation tumor ratios (CTRs), and to explore whether GGOs could be stratified according to CTR with an increment of 0.25 based on its prognostic role. Methods: We retrospectively evaluated patients with clinical stage IA GGOs who underwent curative resection between 2011 and 2016. The patients were divided into 4 groups according to CTR step by 0.25. Cumulative survival rates were calculated by the Kaplan-Meier method. Univariate and multivariate Cox regression analyses were conducted to obtain the risk factors on relapse-free survival (RFS). The surv_function of the R package survminer was used to determine the optimal cutoff value. Receiver operating characteristic (ROC) analysis was generated to validate optimal cutoff points of factors. Results: A total of 862 patients (608 women; median age, 59y) were included, with 442 patients in group A (CTR≤0.25), 210 patients in group B (0.25